Computational Fluid Dynamics Study of Heat Transfer Enhancement in a Circular Tube using Nanofluid - M. Kh., Abdolbaqi; Azmi, W. H.; R., Mamat (Penerbit Universiti Malaysia Pahang, 2015)
A study of computational fluid dynamics has been conducted to study the characteristics of the heat transfer and friction factor of CuO/water & Al2O3/water nanofluid flowing inside straight tube. The three dimensional realizable k-e turbulent model with enhanced wall treatment was utilized. As well as were used Temperature dependent thermophysical properties of nanofluid and water. The evaluation of the overall performance of the tested tube was predicated on the thermo-hydrodynamic performance index. The obtained result showed that the difference in behaviour depending on the parameter that has been selected to compare the nanolfuid with the base fluid. In addition, the friction factor anf the heat transfer coefficient increases with an increase of the nanoparticles volume concentration at the same Reynolds number.